Establishment of In Vitro Cultures and Genetic Fidelity Analysis in Valeriana jatamansi -a High Value Endangered Medicinal Herb - Sharma, Sneh; Sharma, Sakshi; Sharma, Vivek (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted in the Department of Biotechnology, College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India during 2018–2020 for 18 months to develop an efficient, rapid and reproducible protocol for in vitro establishment along with analysing antioxidant activity. In the present study, surface sterilization protocol was standardized using Sodium hypochlorite and mercuric chloride as sterilant. Maximum direct shoot induction frequency from nodal explant was achieved on Murashige and Skoog medium enriched with BAP (5.0 mg l-l), TDZ (3.0 mg l-l) and NAA (1.0 mg l-l) for 18 days. Microshoots inoculated on MS media supplemented with 4.0 mg l-l BAP, 2.0 mg l-l TDZ, 1.0 mg l-l NAA and 0.5 mg l-l GA3) showed maximum frequency of shoot multiplication with average shoot length (4.36±0.08 cm) and average shoot number (14.00±0.57). A 75.00±1.15% rooting with significantly high mean root number (8.00±0.57) and root length was achieved in full strength MS medium, supplemented with same concentration i.e. 4.0 mg l-l BAP, 2.0 mg l-l TDZ, 1.0 mg l-l NAA and 0.5 mg l-l GA3) combination. Maximum plantlets survive after 1 year of acclimatization. RAPD and ISSR markers were used to confirmed genetic stability of in vitro raised plants by showing 100% monomorphism. High multiplication rate associated with genetic stability ensure the efficacy of the present in vitro clonal propagation protocol of this important medicinal plant.